2012 White Paper on Recent Issues in Bioanalysis and Alignment of Multiple Guidelines. (September 2012) - DeSilva, Binodh; Garofolo, Fabio; Rocci, Mario; Martinez, Suzanne; Dumont, Isabelle; Landry, France; Dicaire, Catherine; Szekely-Klepser, Gabriella; Weiner, Russell; Arnold, Mark; Bansal, Surendra; Bateman, Kevin; et al.
Over 400 professionals representing pharmaceutical companies, CROs, and multiple regulatory agencies participated in the 6th Workshop on Recent Issues in Bioanalysis (WRIB). Like the previous sessions, this event was in the format of a practical, focused, highly interactive and informative workshop aiming for high-quality, improved regulatory compliance and scientific excellence. Numerous 'hot' topics in bioanalysis of both small and large molecules were shared and discussed, leading to consensus and recommendations among panelists and attendees representing the bioanalytical community. The major outcome of this year's workshop was the noticeable alignment of multiple bioanalytical guidance/guidelines from different regulatory agencies. This represents a concrete step forward in the global harmonization of bioanalytical activities. The present 2012 White Paper acts as a practical and useful reference document that provides key information and solutions on several topics and issues in the constantly evolving world of bioanalysis.